Problems on damages in the toilet: a study on design and specification of UiTM toilet / Nur Suriya Farah Fadzil - Farah Fadzil, Nur Suriya (2007)
The resulted were obtainable from primary data based on case study and questionnaire and secondary data from observation, journal and book. In the study, all data collected though observation and questionnaire were analyzed and converted to the chart besides the entire defects found through observation were determine. From the result (finding), the major defects that can be found in the toilet UiTM are the equipment can’t function, the flush pump is leaking and it cover missing, floor trap cover missing and it diameter is not following standard requirement, ceiling cover is missing and sometime have dampness and the last defect is floor area is unclean properly so the toilet itself become smelly.